UNDERSTANDING TYPOLOGY AND RELIGIOUS ATTITUDE OF BIMANESE STUDENTS IN UIN ALAUDDIN MAKASSAR - Abdullah Abdullah (JICSA : Journal of Islamic Civilization in Southeast Asian, 2019)
This article discusses the typology of understanding and the level of diversity of students from Bima district in UIN Alauddin Makassar. The research suggest that the reality of their understanding and religious attitudes consist of several categories: First, the tendency to understand the average Makassar UIN Alauddin student from Bima district to the doctrine of salvation for other religions is quite moderate or inclusive. Then from the four sub-variables of this study indicate that in the two sub-variables the respondents' answers showed a positive tendency, regarding Islamic variables and intellectual discourse and sub perceptual variables about acts of violence in the name of religion. Second, these two sub-variables show a moderate religious understanding and attitude from the respondents which is shown by an appreciative attitude towards the use of intellectual discourse in Islamic studies. The three perception variables about acts of violence in the name of religion, students from Bima UIN Alauddin Makassar have a moderate tendency, and evident from the answers of most respondents to the phenomenon of acts of violence in the name of religion. Fourth, the totality in this sub-variable shows the moderate attitude of respondents who reject all forms of coercion and violence in fighting for religion.